2008
DOI: 10.1210/en.2008-0531
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in RET/PTC3 and E7 Transgenic Mouse Thyroids: RET/PTC3 But Not E7 Tumors Are Partial and Transient Models of Human Papillary Thyroid Cancers

Abstract: We studied gene expression profiles in two mouse models of human thyroid carcinoma: the Tg-RET/PTC3 (RP3) and Tg-E7 mice. RP3 fusion gene is the most frequent mutation found in the first wave post-Chernobyl papillary thyroid cancers (PTCs). E7 is an oncoprotein derived from the human papillomavirus 16 responsible for most cervical carcinoma in women. Both transgenic mice develop thyroid hyperplasia followed by solid differentiated carcinoma in older animals. To understand the different steps leading to carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…On comparing the genetic profiles by microarray analysis of these murine tumors to human PTC, the similarities were most congruent when using mouse PTC tumors at a young age (i.e., 2 months) (50). In particular, mouse and human PTCs had similar patterns of overexpression of genes involved in cell cycle, DNA repair, and genes associated with the immune response (50). As proof-ofconcept that these mice are a model for human PTC, both also had similar patterns of expression for proteins involved in the MAPK pathway.…”
Section: Ret=ptc Mutationsmentioning
confidence: 78%
“…On comparing the genetic profiles by microarray analysis of these murine tumors to human PTC, the similarities were most congruent when using mouse PTC tumors at a young age (i.e., 2 months) (50). In particular, mouse and human PTCs had similar patterns of overexpression of genes involved in cell cycle, DNA repair, and genes associated with the immune response (50). As proof-ofconcept that these mice are a model for human PTC, both also had similar patterns of expression for proteins involved in the MAPK pathway.…”
Section: Ret=ptc Mutationsmentioning
confidence: 78%
“…Gene expression study by microarray technology has shown that important biological processes are differently regulated in the two tumour models: in E7 thyroid cells overexpression of cell cycle genes constitutes the most upregulated process whereas RET PTC3 thyroid cells present an upregulation of human PTC markers, of EGF-like growth factors, and extracellular remodeling genes (Burniat et al, 2008). Similarities with human PTC are observed at a young age but are incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…RET/PTC3 and E7 transgenic mice provided by Dr M Santoro (Napoli) and Dr C Ledent (our Institute) respectively were crossed with wild type C57Bl/6. Both strain progenies were genotyped by PCR (Burniat et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is highly expressed in human and mouse thyroids [5,6]. In fact, pendrin mRNA is one of five most abundant transcripts coding for transmembrane proteins expressed in the human thyroid.…”
Section: Arguments For a Role Of Pendrin In Thyroid Physiologymentioning
confidence: 99%